Relationship between Parenting Pattern with Development Autism Children - Azizah, Eva Nur; Amperiana, Sukma (STRADA : Jurnal Ilmiah Kesehatan, 2019)
The family role to child development is very necessary. Parentshave an autistic child will experience more complex problemsforming personality, behavior and their fulfillmentis needing. The approach was cross sectional. The samples were 30 parents and 30 autistic. The instrument wasused a parenting questionnaire and observation for development. The analysis used contingency coefficient correlation, p-value was 0.017, smaller than α = 0.05 (p <0.05). There was a relationship the association parenting family with development autistic. Parents provide parenting appropriatetheir children without curbing and still paying attention to the child's freedom will be good for the child. Parenting provided to children must be in accordance with the development to needtheir children. The right parenting can provide opportunities for children that they are part of the people in their environment so that children can develop optimally.